Speckle-interferometric phase fringe patterns de-noising by using fringes' direction and curvature. (August 2019) - Jiang, Hanyang; Ma, Yinhang; Su, Zhilong; Dai, Meiling; Yang, Fujun; He, Xiaoyuan
Highlights: A novel adaptive filter is proposed for de-noising phase fringe pattern. The kernel of filtering window is deformable in its size, shape, and direction automatically. Comparing with WFT2F method, the proposed algorithm can perform phase denoising without adjusting parameters multiple times. Abstract: We propose an adaptive filter method based on a deformable window shape to remove the noise of wrapped phase fringe patterns in electronic speckle pattern interferometry (ESPI). The filter kernel automatically adjusts its size, shape, and direction according to the direction and curvature of the phase fringe pattern. The direction of a phase fringe pattern is determined using a gradient-based method. Fringe curvature is estimated based on the calculated direction and fitted phase contours. Simulations were performed to evaluate the proposed method, and the results were compared with those of the 2-D windowed Fourier transform filtering (WFTF) algorithm and the medial filter technique. Simulated and experimental results show that the new approach can provide more effective de-noising for phase fringe patterns compared to the other two methods, using few parameters.